Bank Risk Profile, Good Corporate Governance And Company Values in Banking Companies Go Public in Indonesia - Susi Retna Cahyaningtyas; Elin Erlina Sasanti; Wahidatul Husnaini (Universitas Hayam Wuruk Perbanas, 2017)
The latest Bank Indonesia Regulation No.14/18/PBI/2012 requires bank to have minimum capital of 8%-14% depends on the risk profile of each bank. Therefore, the main objective of this research is to assess whether the total of inherent risk profile of each bank meets the terms of this regulation. In addition, this study aims to examine the impact of inherent risk profile and GCG on the banking company value. The sample in this study is determined by purposive sampling method and resulted in 24 banks or 72 observations during 2011-2013. The results showed that 23 banks had low risk and low to moderate risk, and only one bank had moderate risk. The results also showed that inherent risk profile rating is equivalent to capital adequacy. In other words, inherent risk profile of these banks have complied with Bank Indonesia Regulation No.14/18/PBI/2012. Furthermore, this study indicated that GCG has significant and positive influence on the company value, while the inherent risk has no influence on the company value. Overall, this study suggest that go public banks in Indonesia are one of good alternative means of investment for its soundness as reflected by the fulfillment of minimum capital ratio required by the regulator.